Analysis of the Relations among the Components of Technological Pedagogical and Content Knowledge (Tpack): A Structural Equation Model. (July 2014) - Celik, Ismail; Sahin, Ismail; Akturk, Ahmet Oguz
In the current study, the model of technological pedagogical and content knowledge (TPACK) is used as the theoretical framework in the process of data collection and interpretation of the results. This study analyzes the perceptions of 744 undergraduate students regarding their TPACK levels measured by responses to a survey developed by Sahin (2011). The survey contains seven subscales: Technology knowledge (TK), pedagogy knowledge (PK), content knowledge (CK), technological pedagogy knowledge (TPK), technological content knowledge (TCK), pedagogical content knowledge (PCK), and technological pedagogical and content knowledge (TPACK). These seven subscales form the seven variables of the study. The findings show that teacher candidates with more technology knowledge will have more knowledge in pedagogy and content. Also, pedagogy seems as the only variable that is significantly related to all of the variables presented in the TPACK model. This result suggests that pedagogy is the core knowledge of the TPACK. In the study, technology and content knowledge domains influence the TPACK indirectly. Moreover, only the dyadic knowledge components including the content knowledge are related the TPACK.